2004
DOI: 10.1152/ajpheart.00075.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nanobacterial-like structures in calcified human arteries and cardiac valves

Abstract: Mechanisms mediating vascular calcification remain incompletely understood. Nanometer scale objects hypothesized to be a type of bacteria (nanobacteria) are associated with calcified geological specimens, human kidney stones, and psammona bodies in ovarian cancer. Experiments were designed to evaluate human vascular tissue for the presence of similar nanometer-scale objects. Calcified human aneurysms ( n = 8), carotid plaques ( n = 2), femoral arterial plaques ( n = 2), and cardiac valves ( n = 2) and noncalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
145
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 47 publications
6
145
0
5
Order By: Relevance
“…It should be noted that most studies using 8D10 and 5/3 antibodies have actually focused on ELISA (5) and tissue or cell culture immunostaining (7). Miller et al (10) showed that the antibody 8D10 reacts against one single band of 50 kDa from cell pellets prepared under reducing and denaturing conditions comparable with our experiments.…”
Section: Nanobacteria-specific Antibodies React With Human Serum Albuminsupporting
confidence: 90%
See 2 more Smart Citations
“…It should be noted that most studies using 8D10 and 5/3 antibodies have actually focused on ELISA (5) and tissue or cell culture immunostaining (7). Miller et al (10) showed that the antibody 8D10 reacts against one single band of 50 kDa from cell pellets prepared under reducing and denaturing conditions comparable with our experiments.…”
Section: Nanobacteria-specific Antibodies React With Human Serum Albuminsupporting
confidence: 90%
“…We were also intrigued by earlier publications describing the use of monoclonal antibodies specific for nanobacteria, now commercially available through Nanobac Oy (3,10). These antibodies were obtained from splenocyte hybridoma cells of mice that were immunized with purified nanobacteria of bovine origin and fused with the myeloma strain P3 ϫ 63-Ag-8.653 (10).…”
Section: Nanobacteria-specific Antibodies React With Human Serum Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nanobacterium sanguineum is the main causative organism which is engulfed by phagocytes in the body and due to its low virulence it bypasses the body defences and starts its multiplication. 37 The most peculiar feature of these bacteria is formation of slime-like biofilm, which may contribute to the 'stickiness' of the calcifying nanoparticle complex (cell-like vesicles and associated apatite precipitates) in human tissue. 37 Biofilm links together the cell-like nanoparticles and provides anchoring to fixed structures such as arterial walls or kidney tissue.…”
Section: Life Cycle For Calcifying Nanoparticlesmentioning
confidence: 99%
“…37 The most peculiar feature of these bacteria is formation of slime-like biofilm, which may contribute to the 'stickiness' of the calcifying nanoparticle complex (cell-like vesicles and associated apatite precipitates) in human tissue. 37 Biofilm links together the cell-like nanoparticles and provides anchoring to fixed structures such as arterial walls or kidney tissue. It shields the bacterium against host defences helps in colonization and provides an inherent shelter for the growth of nanobacteria.…”
Section: Life Cycle For Calcifying Nanoparticlesmentioning
confidence: 99%